2019
DOI: 10.1177/2322093719838076
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and Its Impact on Business Education in Emerging Economies: A Case of India

Abstract: The article reviews the impact of globalization on the quality of contemporary business education in India. When the Indian government liberalized the business education market in the 1990s, it was assumed that creation of business schools would automatically lead to employment-ready individuals, especially in managerial roles. On the contrary, certain trends suggest that business schools have been producing suboptimally skilled individuals for the industry, leading to an incessantly widening skill–employabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…As an area of ongoing research, the subject of MBA graduate employability has received substantial interest. Earlier studies have suggested that bridging the employability and skills gap is critical for MBA graduates (Abrahamson et al , 2016; Agarwal et al , 2019; Ayoubi et al , 2017; Benson et al , 2014; Bhatia and Panneer, 2019). Available literature also indicates that “communication, interpersonal skills, problem-solving, leadership, creativity, emotional intelligence, entrepreneurship, team-orientation, professionalism, work ethics and previous work experience” are essential skills that improve the employability of MBA graduates (Bhatnagar, 2021; Jackson, 2010).…”
Section: Literature Review and Theoretical Underpinningmentioning
confidence: 99%
“…As an area of ongoing research, the subject of MBA graduate employability has received substantial interest. Earlier studies have suggested that bridging the employability and skills gap is critical for MBA graduates (Abrahamson et al , 2016; Agarwal et al , 2019; Ayoubi et al , 2017; Benson et al , 2014; Bhatia and Panneer, 2019). Available literature also indicates that “communication, interpersonal skills, problem-solving, leadership, creativity, emotional intelligence, entrepreneurship, team-orientation, professionalism, work ethics and previous work experience” are essential skills that improve the employability of MBA graduates (Bhatnagar, 2021; Jackson, 2010).…”
Section: Literature Review and Theoretical Underpinningmentioning
confidence: 99%
“…Although several researchers have suggested the essential skill set required for an MBA graduate to become employable (Ayoubi et al , 2017; Benson et al , 2014) and many studies have examined the gaps and lacuna that exists in the Indian MBA program (Pandiyan, 2011; Bansal and Agarwal, 2019; Bhatia and Panneer, 2019), there is no concrete analytical and quantitative evidence that explores and identifies specific factors that affect employability of a management graduate. A machine learning (ML) model can immensely help in identifying the factors that influence employability (Bharambe et al , 2017; Piad et al , 2016; Othman et al , 2018; Alghamlas and Alabduljabbar, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some researchers have identified essential skills required by the industry for MBA graduates (Benson et al, 2014;Ayoubi et al, 2017). Several studies have also examined the cause of the skill gap in MBA education programmes of B-schools in India (Pandiyan, 2011;Bansal and Agarwal, 2019;Bhatia and Panneer, 2019). Webster and Watson (2002) stated that when a body of research exists on a specific topic, a thorough review of such studies that synthesises and integrates existing research articles stimulates further research on the subject.…”
Section: Literature Reviewmentioning
confidence: 99%